Effect of Board Characteristics, Capital Structure on Firm Performance and Value - Wahyu Febri Ramadhan Sudirman; Anggun Pratiwi; Ravi Adams (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
The board of directors is one of the components of corporate governance used by the company to improve the firm's performance both in the long and short term so that the characteristics of the board become one of the key factors to running a good governance system for the company, even though having a good board composition is not always makes the company have a good performance because of the conflict of interest that occurs between the principal and the manager of the company so that there is a need for an in-depth study of the impact of capital structure on company performance. This study attempts to assess specifically the characteristics of the board (board size, board diversity, and audit committee) owned by the company to capital structure, then confirmed the effect of capital structure on firm performance and firm value by using ROE for performance and Tobin’s Q for firm value. Was used in the study sample 25 a company that had always entered into the LQ45 index within a time frame of 2015-2019. The technique of analysis that was used in this study was Path Analysis. The results of the testing of hypotheses found that board size and audit committee had a positive impact on capital structure, while board diversity had a negative effect on capital structure, then capital structure had a positive effect on firm performance, otherwise, the capital structure had a negative effect on firm value